2010
DOI: 10.1016/j.jmbbm.2010.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of dentin–enamel mechanical properties due to dental whitening treatments

Abstract: The mechanical properties of dentin and enamel affect the reliability and wear properties of a tooth. This study investigated the influence of clinical dental treatments and procedures, such as whitening treatments or etching prior to restorative procedures. Both autoclaved and non-autoclaved teeth were studied in order to allow for both comparison with published values and improved clinical relevance. Nanoindentation analysis with the Oliver-Pharr model provided elastic modulus and hardness across the dentin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 31 publications
(42 reference statements)
2
28
0
2
Order By: Relevance
“…Research indicates that the loss or denaturation of enamel proteins causes increased surface roughness (ZIMMERMAN et al, 2010). This coupled with other factors, such as: enamel composition, water absorption rate, permeability changes and irregularities on the enamel after the dental bleaching procedure may be responsible for the recurrence of extrinsic staining (HEGEDUS et al, 1999.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research indicates that the loss or denaturation of enamel proteins causes increased surface roughness (ZIMMERMAN et al, 2010). This coupled with other factors, such as: enamel composition, water absorption rate, permeability changes and irregularities on the enamel after the dental bleaching procedure may be responsible for the recurrence of extrinsic staining (HEGEDUS et al, 1999.…”
Section: Discussionmentioning
confidence: 99%
“…LIA MONDELLI et al, 2015DE ABREU et al, 2011). These changes may be partly due to the loss or denaturing of protein (ZIMMERMAN et al, 2010) and facilitate the recurrence of extrinsic staining ( JOINER, 2004. NATHOO, 1997 (KARADAS;SEVEN, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Histochemical and morphological alterations to enamel and dentin , changes in the biomechanical properties of human dentin (i.e. ultimate tensile strength, micropunch shear strength, and microhardness) , and alterations in the organic component of dentin have been consistently described. Despite the fact that these were considered, in general, to be minor and not clinically relevant , in 2013, Sato and co‐workers demonstrated that a bleaching agent containing 35% hydrogen peroxide induces a significant in vivo alteration both in enamel and dentin, which could potentially trigger biological and/or mechanical responses in dental structures.…”
Section: Dentin Management: Chemical Treatments Altering the Integritmentioning
confidence: 97%
“…Hydrogen peroxide is a powerful oxidant and several studies have reported microstructural alterations in dental hard tissues induced by bleaching . Histochemical and morphological alterations to enamel and dentin , changes in the biomechanical properties of human dentin (i.e. ultimate tensile strength, micropunch shear strength, and microhardness) , and alterations in the organic component of dentin have been consistently described.…”
Section: Dentin Management: Chemical Treatments Altering the Integritmentioning
confidence: 99%
“…The reduction in bond strength has been attributed to the presence of residual oxygen within the tooth structure [5,7] preventing polymerization of the adhesive monomers, alteration in mineral and protein content [8,9] and the capacity of the bleaching agent to influence the formation of resin tags, structures responsible for micromechanical bond of resin composites to tooth structure. When the bond technique is performed immediately after conclusion of the dental bleaching session, the absence of tags or formation of shorter tags has been observed [10,11].…”
Section: Introductionmentioning
confidence: 99%